Association of Apical Longitudinal Rotation with Right Ventricular Performance in Patients with Pulmonary Hypertension: Insights into Overestimation of Tricuspid Annular Plane Systolic Excursion. Issue 2 (29th December 2015) - Motoji, Yoshiki; Tanaka, Hidekazu; Fukuda, Yuko; Sano, Hiroyuki; Ryo, Keiko; Sawa, Takuma; Miyoshi, Tatsuya; Imanishi, Junichi; Mochizuki, Yasuhide; Tatsumi, Kazuhiro; Matsumoto, Kensuke; Emoto, Noriaki; et al.
Abstract : Background: Current guidelines recommend the routine use of tricuspid annular plane systolic excursion (TAPSE) as a simple method for estimating right ventricular (RV) function. However, when ventricular apical longitudinal rotation (apical‐LR) occurs in pulmonary hypertension (PH) patients, it may result in overestimated TAPSE. Methods: We studied 105 patients with PH defined as mean pulmonary artery pressure >25 mmHg at rest measured by right heart cardiac catheterization. TAPSE was defined as the maximum displacement during systole in the RV‐focused apical four‐chamber view. RV free‐wall longitudinal speckle tracking strain (RV‐free) was calculated by averaging 3 regional peak systolic strains. The apical‐LR was measured at the peak rotation in the apical region including both left and right ventricle. The eccentricity index (EI) was defined as the ratio of the length of 2 perpendicular minor‐axis diameters, one of which bisected and was perpendicular to the interventricular septum, and was obtained at end‐systole (EI‐sys) and end‐diastole (EI‐dia). Twenty age‐, gender‐, and left ventricular ejection fraction‐matched normal controls were studied for comparison. Results: The apical‐LR in PH patients was significantly lower than that in normal controls (−3.4 ± 2.7° vs. −1.3 ± 1.9°, P = 0.001). Simple linear regression analysis showed that gender, TAPSE, EI‐sys, and EI‐dia/EI‐sys were associated with apical‐LR, but RV‐free was not. Multiple regression analysis demonstrated that gender, EI‐dia/EI‐sys, and TAPSE were independent determinants of apical‐LR. Conclusions: TAPSE may be overestimated in PH patients with clockwise rotation resulting from left ventricular compression. TAPSE should thus be evaluated carefully in PH patients with marked apical rotation.